How to promote GBTs innovation through multi-agent collaboration: An evolutionary game system simulation approach - Ma, Yingying; Wang, Qin; Chen, Yingdie; Ma, Minglu; La, Ruifang; Yao, Wenyan; Shang, Sinan; Cui, Ziyi (E3S web of conferences, 2024)
Facing the serious pollution and carbon emission problem, China actively develops and applies GBTs (green building technologies) to realize the dual-carbon target, while the innovation of GBTs is deeply influenced by multiple subjects and factors. This study constructs a tripartite evolutionary game model of GACEs-ARIs, analyzes the inner mechanism of the collaborative innovation process of GBTs through simulation. It is found that: (1) GA is the most crucial subject in the process of collaborative innovation, which plays the role of coordinating the decision-making of the rest of subjects; (2) The trust degree and the benefit distribution coefficient are the influencing factors that play an important role in determining the start and continuation of collaborative innovation; (3) To actively promote the collaborative innovation of GBTs, GA should play a good role as an intermediary to ensure that the trust between the two sides is at a high level, and negotiate a reasonable distribution ratio, actively mobilizing the cooperation of CEs and ARIs by incentives and penalties.